Red nucleus connectivity as revealed by constrained spherical deconvolution tractography. (28th July 2016) - Milardi, Demetrio; Cacciola, Alberto; Cutroneo, Giuseppina; Marino, Silvia; Irrera, Mariangela; Cacciola, Giorgio; Santoro, Giuseppe; Ciolli, Pietro; Anastasi, Giuseppe; Calabrò, Rocco Salvatore; Quartarone, Angelo
Highlights: Assessing neural connectivity of the red nucleus in humans. The red nucleus showed several cortical and subcortical connections. The physiology of red nucleus is discussed. Abstract: Previous Diffusion Tensor Imaging studies have demonstrated that the human red nucleus is widely interconnected with sensory-motor and prefrontal cortices. In this study, we assessed red nucleus connectivity by using a multi-tensor model called non- negative Constrained Spherical Deconvolution (CSD), which is able to resolve more than one fiber orientation per voxel. Connections of the red nuclei of fifteen volunteers were studied at 3 T using CSD axonal tracking. We found significant connectivity between RN and the following cortical and subcortical areas: cerebellar cortex, thalamus, paracentral lobule, postcentral gyrus, precentral gyrus, superior frontal gyrus and dentate nucleus. We confirmed that red nucleus is tightly linked with the cerebral cortex and has dense subcortical connections with thalamus and cerebellar cortex. These findings may be useful in a clinical context considering that RN is involved in motor control and it is known to have potential to compensate for injury of the corticospinal tract.